Synthesis and Antitumor Activity Evaluation of Compounds Based on Toluquinol - Cheng-Sánchez, Iván; Torres-Vargas, José Antonio; Martínez-Póveda, Beatriz Amparo; Guerrero Vásquez, Guillermo A.; Medina, Miguel Ángel; Sarabia-García, Francisco Ramón; Quesada, Ana R. (MDPI, 2019)
Encouraged by the promising antitumoral, antiangiogenic, and antilymphangiogenic properties of toluquinol, a set of analogues of this natural product of marine origin was synthesized to explore and evaluate the effects of structural modifications on their cytotoxic activity. We decided to investigate the effects of the substitution of the methyl group by other groups, the introduction of a second substituent, the relative position of the substituents, and the oxidation state. A set of analogues of 2-substituted, 2,3-disubstituted, and 2,6-disubstituted derived from hydroquinone were synthesized. The results revealed that the cytotoxic activity of this family of compounds could rely on the hydroquinone/benzoquinone part of the molecule, whereas the substituents might modulate the interaction of the molecule with their targets, changing either its activity or its selectivity. The methyl group is relevant for the cytotoxicity of toluquinol, since its replacement by other groups resulted in a significant loss of activity, and in general the introduction of a second substituent, preferentially in the para position with respect to the methyl group, was well tolerated. These findings provide guidance for the design of new toluquinol analogues with potentially better pharmacological properties.
Keywords: Antiangiogénicos; Toluquinol; Thymoquinone; Marine hydroquinone; Natural compound analogues